Study of morphological and physiological characteristics of the tolerant and sensitive mungbean genotypes to shading was carried out in the Station Research of the Indonesian Legume and Tuber Crops Research Institute (ILETRI) from September to December 2004. Nine tolerant genotypes (MMC 87 D-KP-2, MLG 369, MLG 310, MLG 424, MLG 336, MLG 428, MLG 237, MLG 429, and VC2768B) and three sensitive genotypes to shading (Nuri, MLG 460, and MLG 330) were tested in two shading levels, that were without sh - TITIK SUNDARI (HAYATI Journal of Biosciences, 2009)
Study of morphological and physiological characteristics of the tolerant and sensitive mungbean genotypes to shading was carried out in the Station Research of the Indonesian Legume and Tuber Crops Research Institute (ILETRI) from September to December 2004. Nine tolerant genotypes (MMC 87 D-KP-2, MLG 369, MLG 310, MLG 424, MLG 336, MLG 428, MLG 237, MLG 429, and VC2768B) and three sensitive genotypes to shading (Nuri, MLG 460, and MLG 330) were tested in two shading levels, that were without shading and shading of 52%. The randomized complete block design with three replications analysis. The results showed that leaf characters of shading tolerant and sensitive genotypes were different. The shading tolerant mungbean genotypes had good response to light stress so that the growth and development of the leaves were better than that of sensitive genotypes. The shading tolerant mungbean genotypes had bigger and thicker leaves than that of sensitive genotypes. The shading treatments caused reducing rate of PAR absorption, transpiration, photosynthesis, and CO2 stomata conductance. The reduction of all parameters in tolerant genotype was smaller than that of sensitive genotype. The specific leaf area at  four weeks after planting could be used as shading tolerant indicator of mungbeans.         Key words: mungbean, characteristics, morphology, physiology, leaves, tolerant, sensitive, shading